2009
DOI: 10.1111/j.1360-0443.2009.02766.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of successful chronic hepatitis C case finding among patients receiving opioid maintenance treatment in a primary care setting

Abstract: Aims  Injection drug users are at high risk for chronic hepatitis C virus infection (CHC). Opioid maintenance treatment (OMT) offers a unique opportunity to screen for CHC. This study proposed the hypothesis that a general practitioner (GP) with special interest in addiction medicine can achieve CHC screening rates comparable to specialized centres and aimed to investigate determinants for a successful CHC case finding in a primary care setting.Design and participants  Retrospective medical record analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Well‐structured MMTPs, with attributes such as access to mental health professionals and general medical staff, likely have advantages for HCV evaluation and treatment over those without such services. Consistent with the findings of prior studies [11,29], we found that men who were engaged in the MMTP for 36 months or more were significantly more likely to appear in the hepatitis clinic than those with shorter duration of opiate substitution therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Well‐structured MMTPs, with attributes such as access to mental health professionals and general medical staff, likely have advantages for HCV evaluation and treatment over those without such services. Consistent with the findings of prior studies [11,29], we found that men who were engaged in the MMTP for 36 months or more were significantly more likely to appear in the hepatitis clinic than those with shorter duration of opiate substitution therapy.…”
Section: Discussionsupporting
confidence: 91%
“…OR 1.02 37 months =2.0) of getting started CHC treatment compared to a patient simply fulfilling the inclusion criteria of minimum 3 months on substitution. This beneficial effect of OMT has already been shown to increase adherence and virological success in HIV treatment [16,18] and is in line with the finding that an ongoing OMT significantly increased the chance of a successful CHC case finding [19]. We are not aware of a study that has assessed the specific role of an OMT programme in the context of CHC treatment initiation.…”
Section: Discussionsupporting
confidence: 75%
“…A detailed description of the study population and the setting has been previously reported elsewhere [19]. Briefly, all patients ≥ 18 years old and participating for at least 3 months in an official office-based OMT programme run by a single-handed general practice located in Zurich, Switzerland were eligible for CHC assessment and evaluation for antiviral therapy in the case of a CHC infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Senn and colleagues provide an encouraging offer of a successful model for the first stage of the process of identifying those at risk, diagnosing the presence of the disorder and starting treatment. They show clearly the value of opiate substitute treatment in engaging this risk group and the association of this therapy with a successful outcome in testing [7]. This experience of using the attraction of this treatment to encourage a wider health care agenda is not new, and some feel that it is coercive, but as with other harm reduction measures the end undoubtedly justifies the means.…”
mentioning
confidence: 99%